2014
DOI: 10.1152/jn.00789.2013
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ethanol on glycinergic synaptic currents in mouse spinal cord neurons

Abstract: Ethanol increased the frequency of miniature glycinergic currents [miniature inhibitory postsynaptic currents (mIPSCs)] in cultured spinal neurons. This effect was dependent on intracellular calcium augmentation, since preincubation with BAPTA (an intracellular calcium chelator) or thapsigargin [a sarco(endo)plasmic reticulum Ca(2+)-ATPase (SERCA) pump inhibitor] significantly attenuated this effect. Similarly, U73122 (a phospholipase C inhibitor) or 2-aminoethoxydiphenyl borate [2-APB, an inositol 1,4,5-trisp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
27
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 37 publications
8
27
0
Order By: Relevance
“…Additional analysis found that low ethanol concentrations (#50 mM) potentiate glycinergic currents by increasing the apparent affinity of GlyR with no change in efficacy (Aguayo et al, 1996;Crawford et al, 2007;Perkins et al, 2008), and showed that alcohol effects on glycinergic currents were developmentally regulated in cultured spinal neurons (Tapia et al, 1997;Tapia and Aguayo, 1998). Other studies have demonstrated that ethanol affects GlyR expressed in hypoglossal motoneurons (Eggers and Berger, 2004;Aguayo et al, 2014), the spinal cord (Celentano et al, 1988;Mariqueo et al, 2014), and ventral tegmental area neurons (Ye et al, 2001).…”
Section: Molecular Sites For the Functional Regulation Of Glyrmentioning
confidence: 99%
“…Additional analysis found that low ethanol concentrations (#50 mM) potentiate glycinergic currents by increasing the apparent affinity of GlyR with no change in efficacy (Aguayo et al, 1996;Crawford et al, 2007;Perkins et al, 2008), and showed that alcohol effects on glycinergic currents were developmentally regulated in cultured spinal neurons (Tapia et al, 1997;Tapia and Aguayo, 1998). Other studies have demonstrated that ethanol affects GlyR expressed in hypoglossal motoneurons (Eggers and Berger, 2004;Aguayo et al, 2014), the spinal cord (Celentano et al, 1988;Mariqueo et al, 2014), and ventral tegmental area neurons (Ye et al, 2001).…”
Section: Molecular Sites For the Functional Regulation Of Glyrmentioning
confidence: 99%
“…Currently, there is little direct evidence of enhanced or reduced transmitter release from affected regions of the brain or whether excitatory or inhibitory neurons are involved. Multiple studies have measured changes in synaptic transmission between neurons following addition of alcohol, but most propose a postsynaptic target (17,(32)(33)(34). Additionally, the vast majority of studies are done in whole animal or tissue slice preparations where observation of an ethanol effect depends on a sequence of both pre-and postsynaptic events involving many proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, this effect was specific for NMDARs since overexpression of GlyRs did not affect A␤ association to the membrane. This differential effect might be relevant for the disease because GlyRs, unlike NMDARs, are inhibitory proteins that are mainly expressed in spinal cord neurons [45,46], which are believed to be largely unaffected by the disease.…”
Section: Discussionmentioning
confidence: 99%